The Paradox of the Friendly Vengeful Malay - Ramli, Yusri Mohamad (Advances in Social Sciences Research Journal, 2024)
The Malays are commonly known as a very sensitive race compared to other Asian races, if not all races of the world. The sensitivity comes usually in a good way but sometimes in a bad way. The Malays used to be identified by their reputation for vengeance. But authors and researchers on Malays varied in their description that despite admitting to such indignant nature, the Malays are pretty well recognized for their compassion and gentleness. Such contradictory descriptions could be found abundantly in many chronicles of travelers and writers during the 18th and 19th centuries. To better understand the irony, this article attempts to scrutinize the peculiarity of Malay sensitivity, which is signified by the paradox of their kindness and vengeance, by anaylsing the records of observation and encounter of firsthand experiences and direct insights. This study sheds light on how the intricate Malay sensitivity is displayed through their contentment and resentment.